(3GdEaGOI aj Gdabgs - (3CHh GdbGSe GdMSjf Hf Ydj Hf GdMSf GdghSej,J (B421 (3g` s
(3ChdgG (B:s
(3cJGH GdWgGQI HGH GdejGg dGJLhR GdWgGQI HeGA GdhQO hTHgg eeG cGf eYJUQkG ef TF s
(3BNQgG (B:s
(3hef Ydjg eXGde EPG cGf YfO MVhQ GdehJ hde jLO ef jhUi Edjg HbVGFgG cGf fGLjkG YfO Gddg Je s
(3fSNI eUMMIs
(3cJHJ YfGhjjf GdCHhGH hGdahGJM HGdSejcs
(3Ydi WQJgG Jedc HGSe eMeO Hf Ydi Hf bjSs
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3JHUQGJ GdCUd (B:s
Keywords: (3Gdabg GdESdGejs